Potential of Wood Harvesting Residues and Residual Stand Damage due to Timber Harvesting: A Case Study at PT Austral Byna in Central Kalimantan, Indonesia. (12th January 2022) - Suhartana, Sona; Yuniawati,; Gandaseca, Seca; Dulsalam,; Soenarno,; Ratnasingam, Jegatheswaran
Abstract : The practice of timber harvesting in natural forests which has been conducted up to now still leaves wood harvesting residue and residual stand damage. Most condition of wood harvesting residue is still good and can be utilized. The objective of this research was to determine the potency of wood harvesting residue and residual stand damage on timber harvesting in natural forests. The data on wood utilization, wood harvesting residue, and residual damage were collected from three sample plots. The sample plots were arranged in a systematic and purposive manner, and the data were processed with tabulation and average analysis. Research results showed that the average volume of wood being utilized was 9.212 m 3 tree −1 . The average volume of wood harvesting residues was 2.310 m 3 tree −1, and the total average volume of wood harvesting residues which were good, defected, and broken was 2.121 m 3 (80.952%), with an average volume for good wood harvesting residue condition of 1.038 m 3 (34.808%). Proportions of wood harvesting residues were 2.154 m 3 (94.444%) consisting of buttress as large as 0.102 m 3 (5.159%), stumps as large as 0.375 m 3 tree −1 (23.597%), butt as large as 0.855 m 3 (35.930%), and end part as large as 0.821 m 3 (29.758%). The average number of trees with a diameter of 20 cm which were damaged due to felling and skidding was 5 trees ha −1 (5.40%) and 6 trees ha −1 (6.58%), respectively.